Comparison of three protocols for the management of re‐fracture of teeth with uncomplicated crown fractures. Issue 1 (19th September 2021) - Tewari, Nitesh; Tamchos, Rigzen; Chaurasia, Bikash; Rahul, Morankar; Mathur, Vijay Prakash; Goel, Shubhi; Bansal, Kalpana
Abstract: Background: Crown fractures restored by fragment reattachment are liable to re‐fracture, which may cause fragment dislodgement. There is a paucity of literature regarding management of fragment reattachment cases following a further fracture. Hence the aim of the present in‐vitro study was to evaluate and compare the efficacy of three different management protocols for such scenarios. Methodology: Eighty maxillary bovine incisors without structural deformity and with similar dimensions were fractured as per the standard protocol. They were subjected to drying for 24 hours and the fragments were rehydrated by placing them in a humidification chamber for 15 minutes. They were then reattached by using flowable light‐cured composite resin. The teeth (n=20) were fractured again by fixing them in a mechanical frame and using a mallet. They were randomly allocated to three experimental groups. (Group I mechanical abrasion and fragment reattachment, Group II mechanical abrasion, humidification and reattachment, Group III mechanical abrasion and composite restoration, and Group IV positive control with no re‐fracture). The samples were thermocycled and the force required to fracture was tested by using a universal testing machine (Instron‐3360, USA). This was done by applying a tangential load with a speed of 1 mm/min to the teeth with a 500‐kg load cell. Statistical analysis of the results was performed using ANOVA and the independent t‐test. Results: The highest force required to fracture was reported in Group IV (333.26 ± 66.69N) while the lowest was in Group II (254.86 ± 105.23N). The forces in Group I and Group II were 258.36 ± 65.78N and 298.02 ± 97.94N, respectively ( p =0.016, F=3.68). The independent t‐test between the groups revealed a significant difference between Group I and Group IV ( p = 0.001) and Group II and Group IV ( p =0.009). Conclusion: The force required to fracture was significantly lower in the groups involving attachment of the re‐fractured fragments. Among the experimental groups, the group with composite restoration required the highest force to fracture.